Struktur Komunitas Fitoplakton di Kolam Bekas Tambang Emas sebagai Budidaya Ikan - Gusmaweti Gusmaweti; Wince Hendri; Lisa Deswati; Enjoni Enjoni; Vendri Geraldine Kurniawan (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
This study aims to analyze the community structure of phytoplankton in ex-gold mining ponds for fish farming in Nagari Muaro, Sijunjung District, Sijunjung Regency, West Sumatra. The method used is a descriptive survey. Purposive sampling was done by determining the location of the phytoplankton sampling. The results showed that there were three divisions of phytoplankton (Cyanophyta, Chlorophyta and Crysophyta) and 17 genera. The highest relative abundance (KR) was found in the Pediastrum genus of 22.9 with an average diversity index of 3.72, an evenness index of 0.72 and a dominance index of 0.16. The results of the measurement of physical factors, namely the average turbidity of 3.53 NTU, the average water temperature of 32oC and the average water pH of 6. The results of the measurement of the chemical factors of the average water are DO of water of 5.15 ppm, BOD = 1.77 ppm, COD = 26.45 ppm, CO2 = 18.29 ppm and measured levels of mercury (Hg) ranged from 0 – 0.05 ppm. In conclusion, the abundance of phytoplankton is in the low category with a moderate diversity index and the waters are classified as stable. Keywords: Used, Phytoplankton, Community, Pond, Mine Structure